Analisis Biaya dan Waktu Penggunaan Floating Floor sebagai Pengganti Urugan Tanah dengan Metode Value Engineering (VE): Studi kasus Pembangunan Gedung DPRD Kota Mojokerto - Yustian Suhandinata (Fakultas Teknik Universitas Cenderawasih, 2023)
In the Development of Building Activity Budgeting in the Central Government, the construction world has been marked by the construction of increasingly large and complex buildings and other facilities. This is a business opportunity as well as a challenge for the business community, especially the construction services business. The Mojokerto City Government, in this case the Public Works and Spatial Planning Service of Mojokerto City, can be said to be a construction service business actor because the Public Works and Spatial Planning Service is the owner of a project, one of which is the Mojokerto City DPRD Building Construction Project. Where the project is funded by the APBD for one budget year, namely 2020 for the implementation of the work, with an estimated budget of one year. The location for the construction of the building is former agricultural land and with the results of soil tests through sondir boring, there is soft soil with an average thickness of 1.5 m on the surface of the ground. The use of Floating floors can be used as an alternative in the construction of the lower structure of the Mojokerto City DPRD Building. By using the analysis with the Value Engineering method, the results of the initial design Budget Details obtained a total work price of Rp. 10,043,070,000.00 with 28,984 m3 of gravel fill at a cost of Rp. 6,750,501,695.00, with a time required of 99 days, while the alternative Budget Cost produces a total work price of Rp. 9,389,702,000.00 with the soil fill reduced by the concrete slab as wide as the building so that the gravel fill becomes 22,382 m3 at a cost of Rp. 5,212,802,735.00. Thus there is a cost difference of Rp. 1,537,698,960.00 or 21.8% with an implementation time of 77 calendar days and speeding up the work by 22 calendar days. The use of the Floating Floor Structure can be a substitute for soil fill in the construction of the lower structure of the Mojokerto City DPRD building which is more profitable in terms of both cost and time.